Наукова концепція Ф. де Соссюра у світлі нових автографічних матеріалів - Просяник, О.П. (Мовознавство, 2018)
Концепція Ф. де Соссюра відома насамперед у викладі «Курсу загальної лінгвістики», створеного колегами вченого. Опубліковані 2002 р. автографічні матеріали
Соссюра ставлять під сумнів автентичність тексту «Курсу». У статті представлено
короткий нарис історії публікації соссюрівських автографів та ключові відмінності
між викладеними у них поглядами та традиційним розумінням концепції вченого. It is known that the work of the «Course of General Linguistics» was written by
A. Scheche and S. Ballie and contained largely their interpretation of the views of
F. de Saussure. R. Godel’s attempts, who first drew attention to significant conceptual
differences between the text of the «Course» and autographs-notes to lectures and articles,
as well as R. Engler, who compared all handwritten materials with the canonical text
of the «Course of General Linguistics», which made it possible to establish, how the
interpretation by publishers correlate with the original sources of the «Course», did not
have much publicity in the scientific world.
Published in 2002 the autographic Saussure materials confirm that the «Course of
General Linguistics» veils, significantly distorts, and sometimes even contradicts the ideas
of Ferdinand de Saussure. It is found that for F. de Saussure the basic and complete object
of linguistics is not langue (language), namely langage (linguistic activity) as an integral
dynamic system of symbolic relations, as linguosemiotic activity of a person, one of the
forms of his/her semiotic activity. It is established that one of the key categories in the
conception of F. de Saussure is the category of relation. The basic relation that constitutes
each unit of language activity as well as their structural elements in the conception of F. de
Saussure is the difference / distinction (différence). It is found that in contrast to the traditional bialaterial understanding of a sign as a semiotic relation of the concept with an acoustic image, the linguist offers a complex
system of proper semiotic relations of meanings, forms and their differences, connected,
on the one hand, with concepts, and on the other — with the phonetic figures. Neither
concepts (as extra linguistic functions) nor phonetic figures are the parts of semiotic relationship.